2019
DOI: 10.1038/s41598-019-53044-1
|View full text |Cite
|
Sign up to set email alerts
|

Methane and Nitrous Oxide Flux after Biochar Application in Subtropical Acidic Paddy Soils under Tobacco-Rice Rotation

Abstract: Biochar amendment is a good means of mitigating methane (CH4) and nitrous oxide (N2O) emissions. However, the effects of biochar amendment on N2O and CH4 reduction in soil under rotation with different soil moisture contents is not well understood. To understand CH4 and N2O flux from soil with biochar amendment under water-unsaturated and water-saturated conditions, a field experiment was conducted in a tobacco-rice rotation field in subtropical China to investigate N2O and CH4 emissions following soil amendme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 51 publications
(67 reference statements)
1
21
0
1
Order By: Relevance
“…Biochar application (20 t ha −1 ) in this study did not have any effect on SOC or soil pH, whereas it increased the soil DOC, Total N, NH 4 + -N significantly and reduced NO 3 − -N concentrations compared to non-amended soil (Yang et al, 2019). Another study reported that the biochar addition reduced the abundance of methanogenic archaea resulting in lower CH 4 emission (Huang et al, 2019). Beyond its application in the agricultural context, biochar has also gained interest in the waste management industry as a media to enhance control of landfill gas emissions.…”
Section: Carbon Sequestration and Ghg Emission Reduction With Biochar Applicationmentioning
confidence: 44%
“…Biochar application (20 t ha −1 ) in this study did not have any effect on SOC or soil pH, whereas it increased the soil DOC, Total N, NH 4 + -N significantly and reduced NO 3 − -N concentrations compared to non-amended soil (Yang et al, 2019). Another study reported that the biochar addition reduced the abundance of methanogenic archaea resulting in lower CH 4 emission (Huang et al, 2019). Beyond its application in the agricultural context, biochar has also gained interest in the waste management industry as a media to enhance control of landfill gas emissions.…”
Section: Carbon Sequestration and Ghg Emission Reduction With Biochar Applicationmentioning
confidence: 44%
“…Pyrolysis biochar (PC, pyrochar) has been intensive studied in carbon sequestration, soil improvement and greenhouse gas mitigation 6,7 . However, PC always has a high pH value, usually ranged from 8-10, depends on different conditions 8 .…”
mentioning
confidence: 99%
“…Regard to the previous studies, methanogenic anaerobic bacteria are the main cause of CH 4 production in soils (Bridgham et al, 2013; Cai et al, 2018), and methanotrophic aerobic bacteria are able to consume the produced CH 4 and convert it to O 2 and CO 2 in the presence of oxygen. The decrease in CH 4 emissions following biochar addition should be associated with a decrease in the ratio of methanogens to methanotrophs, because of increasing soil porosity (Figure 2), better aeration, and increasing oxygen availability induced by biochar functional groups (Huang, Wang, et al, 2019) which support a wide range of aerobic methanotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…The C : N ratio is also an important parameter of biochar that can be used to interpret the effects of biochar on preventing N 2 O emission from soils (Huang, Wang, et al, 2019). The produced biochar from crop residues (such as rice husk or straw) with a C : N ratio > 40 immobilizes nitrogen (Asadi et al, 2021; Y. F. Cui et al, 2017; Singh Mavi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%